Reduction of the quantization error in fuzzy logic controllers by dithering. - Mao, Jie. (University of Ottawa (Canada), 1999)
Dithering technique has been used to reduce the quantization error for more than thirty years. This thesis reviews the theories of quantization and dithering, which explain the effect of dithering from a theoretical point of view. Applying dithering to digital Fuzzy Logic Controller (FLC) is the focus of this thesis. Two applications, FLC for Inverted Pendulum and FLC for Truck Backer-Upper, have been simulated and reported. The results of the simulation demonstrate the positive effect of input signal dithering on the resolution of the digital FLC output, especially for the case of the coarse quantization of the input signal.
Keywords: Engineering, Electronics and Electrical.